Chronic toxicity of palm oil mill effluent on survival growth rate and survival length rate of zebra fish (Danio rerio) larvae - Zulfahmi Ilham; Nafis Badratun; Waliul Perdana Adli; Munawarah (BIO Web of Conferences)
Palm Oil Mill Effluent (POME) presents a significant ecological challenge due to its high organic load and potential toxicity to aquatic ecosystems. This study examines the chronic toxicity of POME on zebrafish (Danio rerio), focusing on its impact on Specific Growth Rate (SGR) and Specific Length Rate (SLR). A Completely Randomized Design (CRD) was employed, involving three treatments : 0 mL/L (control), 0.5 mL/L (10% LC50-96 hours, Treatment A), and 1 mL/L (20% LC50-96 hours, Treatment B). The results showed significant decrease in SGR and SLR across treatments. Specifically, the SGR decreased from 4.40%/day in the control group to 3.33%/day in Treatment A and 2.61%/day in Treatment B. Similarly, the SLR decreased from 1.13%/day in the control to 0.32%/day and 0.35%/day in Treatments A and B, respectively. These findings underscore the ecological risks of POME, highlighting its potential to disrupt aquatic ecosystem health by impairing fish growth. Moreover, they emphasize the importance of improving industrial waste management practices to mitigate environmental harm and promote sustainable aquatic resource management.